Signalling with dividends? : The signalling effects of dividend change announcements: new evidence from Europe - Vieira, Elisabete Simões (2022)
The dividend policy is one of the most debated topics in the finance literature. One of the different lines of research on this issue is based on the information content of dividends, which has motivated a significant amount of theoretical and empirical research. According to the dividend signalling hypothesis, dividend change announcements trigger share returns because they convey information about management’s assessment on firms’ future prospects. We start by analysing the classical assumptions of dividend signalling hypothesis. The evidence gives no support for a positive relation between dividend change announcements and the market reaction for French firms, and only a weak support for the Portuguese and the UK firms. After accounting for non-linearity in the mean reversion process, the global results do not give support to the assumption that dividend change announcements are positively related with future earnings changes. Afterwards, we formulate two hypotheses in order to explore the window dressing phenomenon and the maturity hypothesis, finding some evidence, especially in the UK market, for both of the phenomenon.